Modern techniques for food authentication - Sun, Da-Wen (Elsevier/Academic Press, 2008)
Includes coverage of various spectroscopic technologies, methods based on isotopic analysis and chromatography, DNA, enzymatic analysis, electrophoresis and thermal methods, this book provides a resource on the developments in food authentication. It offers a comprehensive overview of authentication techniques and technology.